2019
DOI: 10.1038/s41467-019-13711-3
|View full text |Cite
|
Sign up to set email alerts
|

Millimetre-long transport of photogenerated carriers in topological insulators

Abstract: Excitons are spin integer particles that are predicted to condense into a coherent quantum state at sufficiently low temperature. Here by using photocurrent imaging we report experimental evidence of formation and efficient transport of non-equilibrium excitons in Bi2-xSbxSe3 nanoribbons. The photocurrent distributions are independent of electric field, indicating that photoexcited electrons and holes form excitons. Remarkably, these excitons can transport over hundreds of micrometers along the topological ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 50 publications
2
22
0
4
Order By: Relevance
“…A recent experimental study reported the evidence of excitonic superfluid phase on the surface of Bi 2−x Sb x Se 3 3D TI. [131] By using scanning photocurrent microscopy, it was shown that photoexcited electrons and holes form charge neutral bound states which propagate over distances of 1 mm at temperatures up to 40 K. There are indications that the observed effect could be explained by the theoretical model discussed in this work. For instance, in Bi 2−x Sb x Se 3 samples the Fermi level is close to the Dirac point which is an important condition for the formation of excitonic state.…”
Section: D Dms: Graphene and Topological Insulatorsmentioning
confidence: 65%
See 2 more Smart Citations
“…A recent experimental study reported the evidence of excitonic superfluid phase on the surface of Bi 2−x Sb x Se 3 3D TI. [131] By using scanning photocurrent microscopy, it was shown that photoexcited electrons and holes form charge neutral bound states which propagate over distances of 1 mm at temperatures up to 40 K. There are indications that the observed effect could be explained by the theoretical model discussed in this work. For instance, in Bi 2−x Sb x Se 3 samples the Fermi level is close to the Dirac point which is an important condition for the formation of excitonic state.…”
Section: D Dms: Graphene and Topological Insulatorsmentioning
confidence: 65%
“…[63] Recently, transport signatures of the excitonic condensate phase have been found on 3D TI surfaces, with critical tem-perature consistent with the values predicted by the theoretical model. [131] Although the existence of the condensate requires rigorous confirmation, this work gives an incentive to use 3D TIs as a model system for further investigation of the transient excitonic states. One interesting problem is the effect of spin-momentum locking on the spin texture of the excitonic states and their dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В спинтронике операция преобразования между спином и зарядом при комнатной температуре реализуется в ТИ на несколько порядков эффективнее, чем тяжелых металлах [7,8]. В термоэлектричестве и электронике рассматривается возможность использования эффекта свертекучести экситонов [9,10].…”
Section: Introductionunclassified
“…В тонкопленочных двухслойных экситонных структурах на основе n-и p-типа Bi 2 Te 3 , разделенных изолирующим слоем, за счет кулоновского взаимодействия электроннодырочных пар на границе полупроводника и изолятора возникают межслоевые экситоны при оптимальных толщинах пленок и изолирующих слоев. По оценкам [10,19] сопротивление, связанное с эффектом кулоновского увлечения, становится существенно меньше, чем сопротивление каждой пленки, подвижность носителей заряда увеличивается на порядок, что позволяет использовать двухслойные экситонные структуры для увеличения термоэлектрической эффективности.…”
Section: Introductionunclassified